2009
DOI: 10.1158/1078-0432.ccr-08-0933
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of BRAF and RET/PTC Dual Mutations Associated with Recurrent Papillary Thyroid Carcinoma

Abstract: Purpose: Papillary thyroid carcinoma (PTC), the most common thyroid malignancy, usually possesses BRAF mutation or rearranged in translation (RET)/PTC rearrangements. PTC usually possesses BRAF mutation or RET/PTC rearrangements. The mutation status of patients with recurrent PTC has never been characterized in a large population. Experimental Design: Mutation status was determined in a cohort of 54 patients with recurrent PTC and analyzed for clinicopathologic relationships. BRAF and ras mutations were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
91
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 39 publications
10
91
0
2
Order By: Relevance
“…Recently, Alzahrani and Xing (2013) also found that BRAF gene mutations in thyroid cancer could predict lymph node metastasis, which is consistent with our results. Furthermore, multivariate regression analysis also suggested that lymph node metastasis and the presence of BRAF V600E mutations were independent predictors for tumor prognosis, which is also in agreement with the literature (Costa et al, 2008;Henderson et al, 2009). As BRAF gene mutations and lymph node metastasis are closely associated with tumor recurrence, pre-operative detection of the mutation and conventional lymph node dissection may help to reduce the recurrence rate (Bozec et al, 2011;Alzahrani and Xing, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, Alzahrani and Xing (2013) also found that BRAF gene mutations in thyroid cancer could predict lymph node metastasis, which is consistent with our results. Furthermore, multivariate regression analysis also suggested that lymph node metastasis and the presence of BRAF V600E mutations were independent predictors for tumor prognosis, which is also in agreement with the literature (Costa et al, 2008;Henderson et al, 2009). As BRAF gene mutations and lymph node metastasis are closely associated with tumor recurrence, pre-operative detection of the mutation and conventional lymph node dissection may help to reduce the recurrence rate (Bozec et al, 2011;Alzahrani and Xing, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Although several studies have found that BRAF gene mutations are closely correlated with thyroid cancer prognosis, few of these studies have come from China (Costa et al, 2008;Gong et al, 2009;Henderson et al, 2009;Xing et al, 2009;Howell et al, 2011). In the present study, we demonstrated that the BRAF V600E mutation is closely related with age, tumor staging, and clinical prognosis.…”
Section: Discussionsupporting
confidence: 53%
“…Both mutations were simultaneously present in 9.3% of patients with recurrent disease, a much higher percentage than the prevalence of dual mutations in primary disease. These findings support the idea that BRAF mutations, as well as dual mutations, are significantly associated with recurrent papillary thyroid carcinoma [23]. A BRAF V600E mutation in patients older than 65 with papillary thyroid cancer has been associated with a higher incidence of recurrence than in younger patients (10% and 2%, respectively).…”
Section: Mutations and Recurrent Thyroid Cancersupporting
confidence: 84%
“…Among several known genetic aberrations of PTC, kinaseactivating mutations in the V-raf murine sarcoma viral oncogene homolog B1 (BRAF) proto-oncogene are the most frequent event, found in nearly half of all PTCs, and the incidence rate of these mutations approaches 80% in recurrent or metastatic PTCs (13)(14)(15). A single amino acid substitution, from valine to glutamic acid at codon 600 (V600E), accounts for approximately 90% of all BRAF mutations (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%